Pregnancy-Specific Concerns and Psychological Impact of COVID-19 on Antenatal Women - Sanjay Singh; Vinod G Nair; Virendra Vikram Singh; Shyamji Tiwari; Devendra Arora; Madhusudan Dey; Ravindu Tiwari; Sreeni V Nair (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: The ongoing COVID-19 pandemic is causing widespread concern, fear, stress, anxiety, and depression throughout the population worldwide. Pregnant women, being a vulnerable group, are grossly affected by these changing environmental scenarios. The spread of Corona Virus infection itself and the subsequent nation-wide lockdown in India, just like many other countries, has caused a serious impact on antenatal patients. The objective of this study was to bring out the specific concerns of pregnant women during the ongoing COVID-19 pandemic and also to assess the prevalence of Depression and Anxiety Disorder owing to the pandemic.